Implementation of School Literacy Movement through Cultivating Reading Interests - Endiyani, Novia (Elementary Education Journal, 2024)
Background:This study aims to determine the implementation and supporting and inhibiting factors of the implementation of the school literacy movement through students' reading interests. Method:This research method uses a descriptive qualitative type. Data collection techniques using interviews, observations and documentation. The research data are primary and secondary data processed using analysis techniques with data reduction steps, data presentation, and data verification. Data validity uses source triangulation and technique triangulation. Result:The results of the study indicate that: 1) Implementation of the school literacy movement through habituation of reading interest includes habituation, learning and development activities. Habituation is done by setting aside 15 minutes, involving parents, providing a class reading corner. Learning is done by directing students to read for 15 minutes through the class reading corner. Development is done by reading books aloud, silently, together, and/or integrated reading (making story maps, using graphic organizers, discussions). 2) Supporting factors are: school residents are aware of the importance of literacy culture, the existence of a library, the latest book collections, reading corners, etc., active participation of school residents, APBS for the procurement of supporting facilities, the number of posters, wall magazines, slogans, the number of competitions, book donations, etc., and participation from parents. Implication:Inhibiting factors include: teachers have not accompanied students during reading time, low interest in reading among students, incomplete books in the reading corner, no bookshelves in the classroom reading corner, and no mandatory schedule for visiting the library. Novelty:This study reveals supporting and inhibiting factors for school literacy movements through students' reading interests.